Estudo da influência do agente quelante e da concentração do európio nas propriedades estruturais e ópticas do YVO4: Eu sintetizado pela rota sol-gel modificada - Oliveira, Matheus Silveira Campos de (2024)
In the present work, the influence of the chelating agent and doping were studied on the structural and optical properties of the YVO4 and YVO4:Eu doping from 1% to 4%, synthesized by the modified sol-gel route using saccharides with different degrees of complexity as ecological chelating agents: glucose, a monosaccharide; sucrose, a disaccharide; and gum arabic, a polysaccharide. The samples structural analyzes from XRD standards showed the desired YVO4 formation, with unique phase for the group of the samples synthesized with glucose, a small Y2O3 secondary phase in the phosphoruses in the sucrose group, and a small Y10V2O20 secondary phase for the gum arabic group. The crystallite average size estimate showed clear difference between the saccharide groups, with the average of the phosphoruses sizes varying from 41 nm to 66 nm, indicating good applicability of the saccharides as ecological chelating agents. The phosphoruses photoluminescent analyzes showed the same behavior regarding Eu3+ -ion typical f-f excitation and 5D0→7FJ emission transitions in the YVO4 matrix for all saccharide groups. In the excitation and emission spectra of the glucose and sucrose groups, a luminescent quenching effect was observed. This effect was observed in the excitation band regarding the overlapping of the absorption of the VO4 3-group and the charge transfer from O2-to the Eu3+. For the sucrose group, different behavior was observed between the excitation and emission spectra as for the intensity as a function of the Europium concentration. The samples with a secondary Y2O3 phase showed increasing in the excitation with increased secondary phase proportion and showed increased emission with increasing Europium concentration. The luminescent lifetimes were close to 1 ms for all phosphoruses and showed clear distinction between the three groups. The lifetimes for the glucose group were less than 1 ms and equal between them while oscillating around 1 ms for the sucrose group and were greater than 1 ms, and clearly different for each sample, in the gum arabic group. Finally, all phosphoruses showed a very close shade, although distinct between the saccharide groups, and close to the standard-RGB red and the red from Y2O2S:Eu commercial phosphorus, suggesting good applicability in LEDs or other luminous devices.